Developing engineering students’ engagement in academic writing classes using corpus-based instruction - Amare Tesfie Birhan; Yenus Nurie (Asian-Pacific Journal of Second and Foreign Language Education, 2024)
Abstract Engagement is a core issue in language teaching and learning. Without the students’ active involvement in the teaching–learning process, educational objectives could not be achieved. Accordingly, the concept of engagement has been the focus of researchers, practitioners, and policymakers. This research examined the effects of corpus-based instruction on engineering students’ engagement in academic writing classes. The participants were 77 randomly selected fourth-year mechanical engineering students. The data were gathered through a self-reflective report and a journal and analyzed through an independent t-test, One-Way ANOVA, and narration techniques. The data showed that students who were instructed via corpus-based instruction improved their behavioral, emotional, and cognitive engagements better than their counterparts; the experimental group enjoyed the activities and actively participated in different academic writing processes. The data also attested that there was a significant statistical difference between the experimental group and the control group engagements. This research implied that EFL teachers should consider genuine and real-life linguistic features and activities when they design academic writing instruction to enhance their engagement during the instruction.